Biomass processing technologies for bioenergy production: factors for future global market - Alazaiza M.Y.D.; Ahmad Z.; Albahnasawi A.; Nassani D.E.; Alenezi R.A. (Institute for Ionics, 2023)
Biomass processing technology plays a key role in the production of bioenergy, which has the potential to reduce carbon emissions and mitigate climate change. This review article presents the current state of biomass processing technology, its potential advantages for bioenergy production, and factors that may influence the future global market. This review begins with an overview of biomass industry and its role in bioenergy production. Various biomass processing techniques, including thermochemical and biochemical methods, are then reviewed, along with their advantages and limitations. Moreover, it discusses current bioenergy market trends in the past, present, and future growth potential. In addition, this article examines the factors that may influence the future global market for biomass processing technology and bioenergy. Factors including technological advancements, regulatory policies, market competition, and global energy demand are discussed. The results emphasize the importance of choosing the appropriate processing technology based on the specific biomass feedstock and desired end product. The need for R&D investments to improve biomass processing technology and increase the efficiency and scalability of bioenergy production is conclusive. The review points out the importance of political support to promote bioenergy adoption and boost market demand. Despite challenges to overcome, the potential advantages of using biomass processing technology to produce bioenergy make it a promising candidate for meeting global energy needs and reducing carbon emissions. This review article provides a comprehensive overview of biomass processing technologies and their potential role in the global bioenergy market. This highlights the importance of continued investment in research and development and supportive policy frameworks to enable bioenergy deployment and accelerate the transition to a more sustainable energy future. © 2023, The Author(s) under exclusive licence to Iranian Society of Environmentalists (IRSEN) and Science and Research Branch, Islamic Azad University.
Keywords: Bioenergy; Biofuel; Biofuel global market; Biological conversion; Thermochemical conversion